(26 - 2x) 5 = 100
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, ( x + 1 ) + ( x + 2 ) + ... + ( x + 199 ) = 0
x + 1 + x + 2 + ... + x + 199 = 0
( x + x + ... + x ) + ( 1 + 2 + ... + 199 ) = 0
199x + 19900 = 0
199x = 0 - 19900
199x = -19900
x = -19900 : 199
x = -100
Vậy ...
b, ( x - 30 ) + ( x - 29 ) + ( x - 28 ) = 11
x - 30 + x - 29 + x - 28 = 11
( x + x + x ) - ( 30 + 29 + 28 ) = 11
3x - 87 = 11
3x = 11 + 87
3x = 98
x = \(\frac{98}{3}\)
Vậy ...
2x2−10x−3x−2x2−26=02x2−10x−3x−2x2−26=0
13x−26=0−13x−26=0
x=−2
`2x^2 + 10x + 3x - 2x^2 = 26`
`<=> 13x = 26`
`<=> x = 2`
Ta có: 2x(x – 5) – x(3 + 2x) = 26
⇔ 2 x 2 – 10x – 3x – 2 x 2 =26
⇔ - 13x = 26
⇔ x = - 2
( 26 - 2x ) = 100 : 5
( 26 - 2x ) = 20
2x = 26 - 20
2x = 6
x = 6 : 2
x = 3
đúng nhé